2016
DOI: 10.5387/fms.2015-20
|View full text |Cite
|
Sign up to set email alerts
|

Swelling-activated and arachidonic acid-induced currents are TREK-1 in rat bladder smooth muscle cells

Abstract: Using the perforated patch voltage clamp, we investigated swelling -activated ionic channels (SACs) in rat urinary bladder smooth muscle cells. Hypo -osmotic (60%) bath solution increased a membrane current which was inhibited by the SAC inhibitor, gadolinium. The reversal potential of the hypotonicity -induced current shifted in the positive direction by increasing external K + concentration. The hypotonicity -induced current was inhibited by extracellular acidic pH, phorbol ester and forskolin. These pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Sevoflurane, as a commonly used anesthetic, is frequently used in animal experiments and clinical practice due to its effectiveness and safety profile. Studies have shown that sevoflurane can activate TREK-1 pathway through an indirect pathway at the cellular level, thereby preventing cell damage caused by ischemia and hypoxia ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane, as a commonly used anesthetic, is frequently used in animal experiments and clinical practice due to its effectiveness and safety profile. Studies have shown that sevoflurane can activate TREK-1 pathway through an indirect pathway at the cellular level, thereby preventing cell damage caused by ischemia and hypoxia ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of GdCl 3 on CVI(F3) was statistically insignificant, the reagent showed a similar tendency of decrease the CVI(F3) in the LCC. These results may be owing to the diverse pharmacological properties of LaCl 3 and GdCl 3 , which have been reported to block two‐P K + channels at the same concentration as that which blocks TRPC (Alshuaib & Mathew, ; Fukasaku, Kimura, & Yamaguchi, ). The significant depression of CVI(F3) by LaCl 3 can be ascribed to the blocking on volume sensitive two‐P K + channels.…”
Section: Discussionmentioning
confidence: 99%
“…The hypotonic challenge causes regulatory compensation and the signaling pathways may also influence the mechanosensitive channel independently of the direct action of the membrane tension. The TREK-1 current was shown to be reduced by hyperosmotic solution in Xenopus oocytes [29], and was suggested to be activated by the extracellular hypoosmotic environment in isolated rat bladder smooth muscle cells [78]. The TRAAK K + current is also activated by the hypotonic challenge [66].…”
Section: Mechanosensitive Properties Of K 2p Channels As Reflected By the Currently Available Methodsmentioning
confidence: 99%